Peningkatan Hasil Belajar Pada Pembelajaran Tematik Terpadu Menggunakan Pendekatan Saintifik di Sekolah Dasar - Mela Wati; Yunisrul Yunisrul (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2022)
This study aims to describe student learning outcomes in integrated thematic learning using a scientific approach in class II SDN 07 Kampung Dalam, Pasaman Regency. This type of research is a classroom action research using qualitative and quantitative approaches. The subjects in this study were teachers and students of class II where the number of male students was 15 and 11 female students. The results showed that a) planning cycle I obtained a value of 82.95% with good qualifications increased in cycle II to 95.45% with very good qualifications, b) implementation of learning aspects of teachers and students in cycle I obtained a value of 81.25% with qualifications both increased in the second cycle to 93.75% with very good qualifications, c) student learning outcomes in the first cycle obtained an average value of 81.62 then increased in the second cycle to 87.42 with a percentage of 92.73% completeness.